Role of carbohydrates in micropropagation of cork oak - Romano, A; Noronha, C; Martins-Loução, M a (Plant cell, tissue and organ …, 1995)
The influences of carbon sources, fructose, glucose, sorbitol and sucrose on shoot proliferation and in vitro rooting of cork oak (Quercus suber L.) were compared at a wide range of concentrations (1-6%, w/v). The highest number of shoots occurred on glucose-containing medium. Nevertheless, we have chosen 3% sucrose which induced a similar rate of proliferation but favoured shoot elongation, permitting an effectively higher number of shoots during transfers. Sorbitol and autoclaved fructose did not stimulate shoot proliferation. Adventitious root formation was strongly dependent on carbohydrate supply. Sorbitol and autoclaved fructose were completely ineffectively on rooting induction. Glucose was the most effective carbon source on rooting promotion followed by sucrose and filter-sterilized fructose. The rooting response induced by fructose was dependent on the sterilizing procedure. The number of adventitious roots produced per shoot increased with increasing glucose and sucrose concentration. The content of reducing sugars in leaves of proliferation cultures and in leaves and roots of rooted plantlets was more dependent on carbon concentration than on glucose or sucrose supplement. The results presented here show that carbohydrate requirements during cork oak micropropagation depend upon the phase of culture. Sucrose (3%) and glucose (4%) were the best carbon sources respectively during proliferation and rooting phases.
Keywords: carbon source; micropropagation; Quercus suber; reducing sugars; rooting